Evaluation of the impact of a food program on the micronutrient nutritional status of argentinean lactating mothers - Varea, Ivana (2012)
This study was conducted to evaluate the impact of a food aid program (Plan Más Vida, PMV) on the micronutrient nutritional condition of lactating mothers 1 year after its implementation. The food program provided supplementary diets (wheat- and maize-fortified flour, rice or sugar, and fortified soup) to low-income families from the province of Buenos Aires, Argentina. A prospective, non-experimental study was carried out to evaluate the micronutrient nutritional status of lactating mothers (n = 178 at baseline and n = 151 after 1 year). Biochemical tests (hemoglobin, ferritin, zinc, vitamin A, and folic acid), anthropometric assessments (weight and height) and dietary surveys (24-h recall) were performed. We found no significant changes in anthropometric values 1 year after the intervention. The risk for vitamin A (retinol 20-30 μg/dl) and folate deficiency significantly decreased 1 year after PMV implementation (56.3 vs. 29.9 and 50.3 vs. 3.4 %, respectively; p < 0.001). Anemia was seen in 25.8 % of lactating mothers at baseline, without statistically significant differences 1 year after (p = 0.439). The nutritional data obtained after assessing the early impact of PMV actions may be useful to provincial health authorities to perform periodic evaluations in the future. © 2012 Springer Science+Business Media New York.